System Approach To The Analysis Of Processes Carrying Out On Technological Line Of Production Of Salted Stone From Apricot Fruits - Yamaletdinova Munira Faditovna., Narziyev Mirzo Saidovich., Hikmatov Doniyor Nematovich. (International Journal of Advanced Science and Technology, 2020)
In this article, the author offers study of the method of systematic approach and analysis for the research of technological processes that promote the opening of interrelated processes, based on a six-step hierarchical structure. The method of multistage system analysis is an analysis with a consistent extension of the system: the system under study is divided into its constituent elements; the process and parameters for the selected item are clarified; system division into subsequent systems of decision-making. Each of the six stages of the hierarchical structure is interrelated with each other, which gives possibility to study the processes and sub-processes separately. In addition, the issue of determining the main processes and sub-processes affecting the efficiency and organization of the technological line for the production of salted stones from the apricot fruits in whole is decided.